2001
DOI: 10.1086/321628
|View full text |Cite
|
Sign up to set email alerts
|

On Turbulent Reconnection

Abstract: We examine the dynamics of turbulent reconnection in two-dimensional and three-dimensional reduced MHD by calculating the e †ective dissipation due to coupling between small-scale Ñuctuations and large-scale magnetic Ðelds. Sweet-Parker type balance relations are then used to calculate the global reconnection rate. Two approaches are employedÈquasi-linear closure and an eddy-damped Ñuid model. Results indicate that despite the presence of turbulence, the reconnection rate remains inversely proportional to as i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…A number of papers have attempted to treat turbulent magnetic reconnection by the formal methods of mean-field electrodynamics (MFE), e.g., Strauss 1988 andKim &Diamond 2001. Before we address these works in any detail, let us briefly discuss the relationships of LV99 itself to MFE.…”
Section: Alternative Ideas On the Role Of Turbulence In Magnetic Recomentioning
confidence: 99%
“…A number of papers have attempted to treat turbulent magnetic reconnection by the formal methods of mean-field electrodynamics (MFE), e.g., Strauss 1988 andKim &Diamond 2001. Before we address these works in any detail, let us briefly discuss the relationships of LV99 itself to MFE.…”
Section: Alternative Ideas On the Role Of Turbulence In Magnetic Recomentioning
confidence: 99%
“…Turbulent reconnection models are still under debate. For instance, Kim & Diamond (2001) concluded that the effect of hyperresistivity is negligible with respect to turbulent diffusivity and that, despite turbulence, the global reconnection rate (that scales as in the Sweet & ParkerYtype reconnection) cannot be given by a simple sum of local reconnection events (as claimed by Lazarian & Vishniac 1999); hence, fast global reconnection cannot be achieved. It has also been proposed that, as the CS is stretched with the CME propagation, recurrent secondary tearing instabilities occurring at different spatial scales lead to a fractal (i.e., scale-free) CS structure (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25] Other studies have shown that laminar neutral sheet reconnection is unstable to two-dimensional linear perturbations via a three-step transition-to-turbulence process. 15,26,27 Here, we investigate a slightly different aspect of the problem, namely how sensitive initial states known to produce reconnection dynamics are to the addition of small-scale turbulence.…”
Section: Introductionmentioning
confidence: 99%